Congress and the Cold War - Johnson, Robert David 1967- (Cambridge University Press, 2006)
The first historical interpretation of the congressional response to the entire Cold War. Using a wide variety of sources, including several manuscript collections opened specifically for this study, the book challenges the popular and scholarly image of a weak Cold War Congress, in which the unbalanced relationship between the legislative and executive branches culminated in the escalation of the U.S. commitment in Vietnam, which in turn paved the way for a congressional resurgence best symbolized by the passage of the War Powers Act in 1973. Instead, understanding the congressional response to the Cold War requires a more flexible conception of the congressional role in foreign policy, focused on three facets of legislative power: the use of spending measures; the internal workings of a Congress increasingly dominated by subcommittees; and the ability of individual legislators to affect foreign affairs by changing the way that policymakers and the public considered international questions
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: United States / Congress / History / 20th century; USA -- Congress; Geschichte 1900-2000; Außenpolitik; Geschichte; Cold War; Legislative oversight / United States / History / 20th century; Ost-West-Konflikt; USA; United States / Foreign relations / 1945-1989